Promulgation of Navigational Warnings Under the Global Maritime Distress and Safety System - Soluri, Elroy A. (The International Hydrographic Review, 2015)
The Global Maritime Distress and Safety System (GMDSS), adopted in 1988, was developed under the auspices of the International Maritime Organization (IMO). The GMDSS will improve the dissemination and receipt of Maritime Safety Information (MSI) by vessels at sea and appropriate shore facilities equipped to render search and rescue coordination to shipping. Operational service of GMDSS began on 1 February 1992, with full implementation scheduled for 1 February 1999. Although there are seven basic categories of MSI within the GMDSS, this paper will focus on the promulgation of long range and coastal navigational warnings, which are coordinated through the International Hydrographic Organization (IHO).